Penyuluhan Kesehatan Mental Pada Mahasiswa Tingkat Akhir Program Studi Farmasi Fakultas MIPA Universitas Lambung Mangkurat - Hayatun Izma; Satrio Wibowo Rahmatullah; Muhammad Ikhwan Rizki; Anna Humaira (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Mental health is as important as physical health. Final year students are inclined for mental health disorders associated with finishing their final project. This activity is to increase student’s knowledge and awareness of mental health so it can stimulate a healthy mental of students who are finishing final projects. This activity began with a pretest session to measure participant’s initial knowledge about mental health, presentation using experiental methods, discussion, sharing and Q&A session, and top it off with a posttest session. The results of this activity showed increase participant’s knowledge about mental health, from 57.84% to 95.47%.